Gilligan and complexity: reinterpreting the “ethic of care” - Yvonne Malan; Paul Cilliers (Acta Academica, 2004)
In In a different voice (1982) Carol Gilligan argues for an “ethic of care”, which she links to a “moral voice” of women. This stance has been criticised as being essentialist and reinforcing gender stereotypes. This article, however, argues that the concept of an ethic of care could be a creative way of approaching ethics in a complex social system. Its position is supported by arguments from deconstruction discourses.